State and society in Papua New Guinea, 2001-2021 - May, R. J. (Ronald James), 1939- (Pacific series., 2022)
"In a previous volume, State and Society in Papua New Guinea: The First Twenty-Five Years (2001, reprinted by ANU E Press in 2004), a collection of papers by the author published between 1971 and 2001 was put together to mark Papua New Guinea's first 25 years as an independent state. This volume presents a collection of papers written between 2001 and 2021, which update the story of political and social development in Papua New Guinea in the first two decades of the twenty-first century. The chapters cover a range of topics, from an evaluation of proposals for political reform in the early 2000s, a review of the discussion of 'failing states' in the island Pacific and the shift to limited preferential voting in 2007, to a detailed account of political developments from the move against Sir Michael Somare in 2011 to the election of Prime Minister Marape and his performance to 2022. There are also chapters on language policy, external and internal security, religious fundamentalism and national identity, and the sustainability of economic growth."--Publisher's description.